BALINESE HINDU WEDDING CEREMONY IS HINDU RITUAL MARRIAGE CEREMONY BASED ON CULTURE AND CUSTOMS - Made Girinata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Balinese Wedding Ceremony is a marriage process carried out using traditional Balinese culture customs by using wedding offering ceremony which is sanctioned by a Brahmin priest or village priest in accordance with the cultural customs of the place where the wedding took place. Balinese Wedding is something that is very sacred and also involves several residents in a village to help run this wedding ceremony, where the families will be busy preparing everything related to this wedding ceremony, Balinese Wedding Ceremony is a unique wedding procession based on Balinese Hindu rituals where the couple will be inaugurated as husband and wife in a spirit realm with using the Banten wedding facilities that have been prepared in advance, so marriage in Bali is a very sacred thing. To be married with someone you love in a very special way should be a special event and held in a very exotic place. Which is why many westerners have been choosing Bali as their place to get married. It has romance, mysticism and a unique culture which will give a very meaningful impression for a lifetime in a marriage using Balinese cultural customs